Archaeological Investigations of the Maldives in the Medieval Islamic Period
1 online resource (362 pages).
Keywords: This book presents pioneering research on the Indian Ocean archipelago of the Maldives in the medieval period. Primarily archaeological, the book has an interdisciplinary slant, examining the material culture, history, and environment of the islands. Featuring contributions by leading archaeologists and material culture researchers, the book is the first systematic archaeological monograph devoted to the Maldives. Offering an archaeological account of this island-nation from the beginnings of the Islamic period, it complements and nuances the picture presented by external historical data, which identify the Maldives as a key player in global networks. The book describes excavations and surveys at a medieval site on the island of Kinolhas. It offers a comprehensive analysis of finds of pottery, glass, and cowries, relating them to regional assemblages to add valuable new data to an under-researched field. The artefacts suggest links with India, Sri Lanka, the Middle East, Arabia, Central Asia, Southeast Asia, and China, offering tangible evidence of wider connections. The research also evidences diet, crafts, and funerary practices. The rigorous presentation of the primary material is framed by chapters setting the context, conceptual approaches and historical interpretation, placing the Maldives within broader dynamics of Islamic and Indian Ocean history and opening the research results to a wide readership. The book is aimed at students and researchers interested in the archaeology and history of the Indian Ocean, Islamic studies, island and coastal communities, maritime networks, and the medieval period, with special relevance for the ⁰́₈Global Middle Ages⁰́₉. It will appeal to art historians, archaeologists, museologists, and heritage and material culture studies researchers with related interests.